PENERAPAN MODEL LEARNING CYCLE 5E PADA MATERI FAKTORISASI EKSPRESI ALJABAR DI KELAS VII SMP NEGERI 2 CAPKALA - Janius, Vebianus; Zubaidah, Zubaidah; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research was aimed to explained the effectiveness of  the Implementation Model Learning Cycle 5E in the Material of Algebraic Expression Factorization Subject in Class VII A SMP Negeri 2 Capkala Academic Year 2018/2019. The aspects that want to be explained, namely: learning outcomes of students; and learning activities of students.This research method is explanatory. The form of research uses Pre-Experimental design with a one-shot case study design. The research subjects were students of class in Class VII A SMP Negeri 2 Capkala Academic Year 2018/2019.  Based on the results obtained from two aspects are (1) learning outcomes of students achieving classical completeness, namely 89.29% of students can achieve minimum completeness criteria; and (2) learning activities of students are categorized as active (69.33%). The final conclusion of this study is the Implementation Model Learning Cycle 5E to the effective in the Material of  Algebraic Expression Factorization Subject in Class VII A  SMP Negeri 2 Capkala Academic Year 2018/2019.  Keywords: Model Learning Cycle 5E, Learning Outcomes, Learning Activities.